Model Evaluasi Penerapan Aspek Pakan dan Air Minum dalam Good Farming Practice Peternakan Domba di UP3J Bogor - M. R. A. Hasan; A. Yani; S. Rahayu (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2022)
Good Farming Practice applied as agovernment-based guideline for good and precise cultivation in raising livestock. The main objective of good farming practice is to increase livestock population, meat production and livestock productivity. Published guidance contained how to apply good farming practices in goats and sheep cultivation, but priority of each aspect is not available. Based on that guidance, 5 main aspects were determined which include aspects of facilities, feed and drinking water, production processes. Unit Pendidikan dan Peternakan Jonggol (Jonggol Animal Husbandry Education and Research Unit), which was established since 1984, has a sheep farm unit with semi-intensive rearing methods, but the current production is less than optimal. This study aimed to examines Good Farming Practice (GFP) appliance at Jonggol Animal Husbandry Education and Research Unit using the Analytical Hierarchy Process (AHP) method to find priority vectors that will be apploed as the basis for the priority weights for each aspect, and then conduct an evaluation model to assess and improve the performance of livestock units in UP3J. The results showed priority aspects of GFP with the highest AHP weight, namely feed and drinking water (weight 0.548). This study shows that the combined value ofobservation and priority vector of the aspects of feed and drinking water is 42.7%. The value represents the implementation of thus aspects of good farming practice categorized as LESS.